Implementation of Turtle Conservation Policy in the Nipah Essential Ecosystem Area for the Sustainability of Aquatic Resources and Environment - Nurul Komarudin; Fahrunnisa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Aquatic resources are one of the natural resources that can be renewed, but if their use is carried out excessively without paying attention to sustainability, it will have a bad impact on the aquatic resources themselves. This study discusses policies related to sea turtle conservation activities, the purpose of this study is to find out the policies that have been made related to sea turtle conservation and its implementation in the field, this is done to realize the sustainability of resources and the aquatic environment. This study was conducted in the Nipah Essential Ecosystem Area (KEE), Malaka Village, North Lombok, West Nusa Tenggara. The existence of this ecosystem area can directly or indirectly help in natural resource conservation activities in the Nipah coastal environment. One of the policies that have been implemented to preserve turtle habitat is by conserving sea turtle habitat, and educational activities on the importance of sea turtles for natural resources and the aquatic environment. Conservation activities carried out in the Nipah Essential Ecosystem Area (KEE) have an implementation score of 100% meaning that policies related to sea turtle conservation in the Nipah Essential Ecosystem Area have been implemented properly, this happens because of the cooperation of various parties between local communities, the TCC (Turtle Conservation Community) community, local governments, and the central government. With a high implementation score, sea turtle habitats will be better preserved, and natural resources and aquatic environments will become sustainable.